Nonverbal Synchrony in Couple Therapy Linked to Clients’ Well-Being and the Therapeutic Alliance - Nyman-Salonen, Petra; Kykyri, Virpi-Liisa; Tschacher, Wolfgang; Muotka, Joona; Tourunen, Anu; Penttonen, Markku; Seikkula, Jaakko (Frontiers in Psychology, 2021)
Nonverbal synchrony between individuals has a robust relation to the positive aspects of relationships. In psychotherapy, where talking is the cure, nonverbal synchrony has been related to a positive outcome of therapy and to a stronger therapeutic alliance between therapist and client in dyadic settings. Only a few studies have focused on nonverbal synchrony in multi-actor therapy conversations. Here, we studied the synchrony of head and body movements in couple therapy, with four participants present (spouses and two therapists). We analyzed more than 2000min of couple therapy videos from 11 couple therapy cases using Motion Energy Analysis and a Surrogate Synchrony (SUSY), a procedure used earlier in dyadic psychotherapy settings. SUSY was calculated for all six dyads per session, leading to synchrony computations for 66 different dyads. Significant synchrony occurred in all 29 analyzed sessions and between the majority of dyads. Complex models were used to determine the relations between nonverbal synchrony and the clients’ well-being and all participants’ evaluations of the therapeutic alliance. The clients’ well-being was related to body synchronies in the sessions. Differences were found between the clients’ and therapists’ alliance evaluations: the clients’ alliance evaluations were related to synchrony between both dyads of opposite gender, whereas the therapists’ alliance evaluations were related to synchrony between dyads of the same gender, but opposite to themselves. With four participants present, our study introduces a new aspect of nonverbal synchrony, since as a dyad synchronizes, the other two participants are observing it. Nonverbal synchrony seems to be as important in couple therapy as in individual psychotherapy, but the presence of multiple participants makes the patterns more complex.